Controlling Anthracnose Disease of Locally Chili in Marginal Wetland using Endophytic Indigenous Microbes and Kalakai (Stenochlaena palustris) Leaf Extract - Ismed Setya Budi; Mariana Mariana (Center for Journal Management and Publication, 2016)
The research aims were to get the indigenus endophytic microbial consortium and to test the potency of kalakai leaf extract as biopesticides and biofertilizer on chili plant specific to wetlands (i.e., var. Hiyung). The microbes capable of inhibiting the growth of anthracnose have been performed on in-vitro test in pairs method. Â It was found that 12 isolates have the ability to inhibit the growth of pathogens. Â However, based on the results of a confirmatory endophytic test only three isolates had positive role as endophytic in chili plants, namely Trichoderma sp DN3, Trichoderma sp AK2, and Trichoderma sp BT1. The results of the effectiveness of each treatment on chilli plants in the greenhouse and the field shows that the application of endophytic could inhibit the development of anthracnose and spur the growth of plants. It could be concluded that the applications of kalakai leaf extract at the rate of 30 mL/plant can function as biopesticides and biofertilizer.